Enhanced dye photocatalysis and recycling abilities of semi-wrapped TiO2@carbon nanofibers formed via foaming agent driving. Issue 2 (1st February 2018) - Liang, Yaohui; Zhou, Baoming; Li, Nan; Liu, Liangsen; Xu, Zhiwei; Li, Fengyan; Li, Jing; Mai, Wei; Qian, Xiaoming; Wu, Ning
Abstract: To enhance photocatalysis and recycling abilities of catalyst simultaneously, novel microstructure in which TiO2 nanoparticles were semi-wrapped in carbon nanofibers (CNFs) was proposed and produced successfully. Betaine was employed as a foaming agent to drive the TiO2 nanoparticles to migrate from inner space to the surface of CNFs gradually under the function of calcination. Various characterizations were used to research the surface and crystal evolution process of TiO2 and CNFs, and the semi-wrapped microstructure of TiO2 @CNFs was well built up when the composites were carbonized at 800 °C. TiO2 was immobilized stably on CNFs while exposed partly to air distinctively. This unique semi-wrapped structure endowed the composites with strong interfacial interaction between TiO2 and CNFs, and the exposed section of TiO2 provided sufficient reaction sites for organic dyes. Notably, photocatalytic degradation ratio of Rhodamine B in the first time reached 98.2% and even remained 95.4% after being recycled for 5 times under the irradiation of ultraviolet light, indicating that the photocatalysis and recycling abilities were obviously strengthened simultaneously compared with other counterparts reported in literature.